Bad Time Stories - YONATAN RESHEF,, CHARLES KEIM (University of Toronto Press, 2014)
In this book we explore how, in the late 1990s and the first decade of the new millennium, Canadian governments and unions mobilized language to frame and justify their viewpoints and conduct during labour conflicts in the public sector. The 1990s have been recognized as â€œthe most stressful decade for public-sector industrial relations since the inception, 25 years earlier, of collective bargaining for public-sector workersâ€ (Swimmer, 2001a: 1). A combination of high deficit and debt had prompted provincial governments to trim budgets, restructure the public sector, and redefine their roles as service providers. One result was a number of notable clashes between governments and unions protesting unprecedented wage rollbacks and layoffs. The new millennium did not bring much relief. Still hobbled by deficits, debts, the rising costs of services, and a slowdown in consumer spending and overall growth, governments kept administering the unsavoury concoction of wage restraints and layoffs. Recently, Ontarioâ€™s Premier Dalton McGuinty said that â€œwe can protect our class size, we can protect full-day kindergarten and we can also protect jobs. But it does require that we put in place the kind of salary freeze that we have proposed to teachersâ€ (Bradshaw and Stuec, 2012). These words were conciliatory relative to what many public-sector workers across Canada had experienced during the first decade of the 2000s, and what they would come to experience over the next few years (Fekete, 2011). Not surprisingly, according to the Conference Board of Canada (Shepherdson, 2011), workers deemed it unfair that governments were attempting to balance the books by cutting public-sector jobs and compensation. With frustrated workers expecting unions to deliver more and little left to bargain over, tension between public sector unions and governments was not abating (ibid.: 14-15).